A nano-LiNbO3 coating layer and diffusion-induced surface control towards high-performance 5 V spinel cathodes for rechargeable batteries - Kim, Hyeongwoo; Byun, Dongjin; Chang, Wonyoung; Jung, Hun-Gi; Choi, Wonchang (ROYAL SOC CHEMISTRY, 2017)
The surface of a spinel LiNi0.5Mn1.5O4 cathode was modified with a nano-LiNbO3 coating layer by employing a Nb citrate-coated Ni0.25Mn0.75(OH)(2) precursor and subsequent single calcination with LiOH at 900 degrees C. The facile formation of the LiNbO3 coating layer in the earlier stage of the calcination process in the presence of abundant LiOH resulted in successful modification of the parent material with a thin and homogeneous coating layer. More importantly, the partial diffusion and subsequent substitution of Nb ions into the parent material beneath the coating layer resulted in a Mn3+-rich domain near the surface of the parent material, LiNi0.5Mn1.5O4. This Mn3+-rich region effectively improved the kinetic properties of Li+ diffusion near the surface of the cathode, especially during fast discharging, and the LiNbO3-coated spinel oxide cathode with a high loading level of around 10 mg cm(-2) exhibited a discharge capacity of 100 mA h g(-1) even at 10C at ambient temperature. In addition, it showed 90% capacity retention after 100 cycles at 60 degrees C owing to the LiNbO3 coating layer acting as a protective layer.
Keywords: HIGH-VOLTAGE SPINEL; ENHANCED LITHIUM STORAGE; HIGH-RATE CAPABILITY; COATED LINI0.5MN1.5O4 SPINEL; VAPOR-DEPOSITION METHOD; ELECTROCHEMICAL PROPERTIES; CYCLING PERFORMANCE; ASSISTED SYNTHESIS; OXYGEN VACANCIES; ETHYLENE-GLYCOL